9/11, foreign threats, political legitimacy, and democratic institutions. Issue 1 (2014) - ,
Abstract : Purpose – The manipulation of fears generated by 9/11 resulted in restrictions of civil liberties. Although this danger to freedom has been descriptively addressed, its deeper causes and dynamics have not received extensive treatment. This article reassesses the political reaction to 9/11 in terms of economic theory and evolutionary biology. The paper aims to discuss these issues.Design/methodology/approach – The explanatory framework is drawn from findings in the economics of war and the biological evolution of war‐like behavior in the human species.Findings – The fact that war and its threat were ever‐present in human evolution resulted in two social propensities that render society vulnerable to political manipulation. External threats dramatically heighten social cohesion as well as loyalty to leaders. In pre‐state societies, all members could clearly witness and judge the nature of an external threat, and because leaders led responses, they were vulnerable to injury or death. In modern highly complex societies, by contrast, the nature of threats is less transparent, and leaders can command far from immediate danger. Consequently, in modern times, leaders can be tempted to generate, especially in times of economic dysfunction, fear of an external threat to rally support and detract attention from otherwise inadequate leadership.Originality/value – This article presents a deeper analysis, grounded in economics and evolutionary biology, of the manner in which political leaders can exaggerate the dangers of foreign threats to enhance their power at the cost of civil liberties. Acknowledgements : JEL classification – A12, N40, Z13, P16